Genotype by Environment Interaction on Early-Maturing and High-Yield Maize Hybrids - Achmad Amzeri; . Suhartono; Gita Pawana; Alfian Ma’arif; Iswanto Suwarno (Journal of Human, Earth, and Future, 2023)
Assembling hybrid maize varieties with early-maturing and high-yield traits is one of the methods to increase maize productivity in drylands in Indonesia. Trials of hybrid maize candidates in several locations and different seasons are highly needed to determine the stability of hybrid maize candidates prior to commercial release. The objectives of the research were: (1) to evaluate the performance of maize hybrids in several locations and different seasons; (2) to assess the stability of early-maturing and grain yield characteristics of genotypes evaluated in several locations and seasons; and (3) to determine hybrid maize candidates that can be released as new superior/elite varieties. The research was conducted at 14 research populations (7 different locations, 2 seasons). Each population was planted according to the randomized block design with 10 genotypes as treatments and 4 replicates, so 40 experiment units were obtained. Ten genotypes were tested: six hybrid maize candidates derived from a diallel cross with high yield potential and early-maturing traits (G1, G2, G3, G4, G5, G6) and 4 elite varieties as checks (G7 = SK, G8 = ANM, G9 = Pertiwi-x, and G10 = BISI-x). The combined analysis of variance (ANOVA) conducted on 10 genotypes and 14 research populations revealed that genotypes, environments (season, location, season x location), and interactions (genotype x season, genotype x location, genotype x season x location) significantly affect harvest age and grain yield per hectare (p < 0.01). G4 had an early harvest age (91.93 days) and grain yield per hectare above the average of all genotypes in all environments (8.71 ton ha-1), and was also declared stable based on three stability analyses: Finlay-Wilkinson, Eberhart-Russel, and AMMI. Thus, G4 is recommended as an elite hybrid maize variety with early-maturing, high-yield, stable, and broad adaptability traits.